Discrimination and Mental Health: Mediation Effects of Coping Strategies in LGB and Heterosexual Youth - Fonseca de Freitas, Daniela; Silva, Cláudia; Coimbra, Susana (Psykhe, 2021)
Previous studies reveal that the negative effect of discrimination on mental health is particularly pernicious among stigmatised minorities. However, research also points out the importance of protection mechanisms that may buffer its effect. This study aimed to explore the relationships between mental health, perceived discrimination, and coping strategies of positive reframing and self-blame in LGB and heterosexual youth. Data were collected through a paper and pencil and an online survey administered to 195 Portuguese adolescents and young adults. The survey covered mental health (Mental Health Inventory-5), discrimination (Everyday Discrimination Scale), and coping strategies (Brief COPE). Of the sample, 73.3% were women and 51.8% self-identified as lesbian, gay or bisexual (LGB). Analyses of variance show that LGB participants have experienced more discrimination than their heterosexual counterparts. There was no difference in the levels of mental health and the use of self-blame or positive reframing coping strategies. Regression analyses reveal that perceived discrimination and self-blame contribute to the worsening of the mental health of LGB and heterosexual youth. Positive reframing coping was a predictor of mental health only in LGB participants, a strategy that contributed to their resilience in the face of discrimination. Additionally, only LGB participants displayed an indirect effect of discrimination on mental health, partially mediated by self-blame coping. Results corroborate previous findings that suggest that perceived discrimination has a more deleterious effect for members of a minority group and support the psychological mediation framework regarding the effect of discrimination on mental health in stigmatised groups.